An Abnormal Host/Microbiomes Signature of Plasma-Derived Extracellular Vesicles Is Associated to Polycythemia Vera - Barone, Monica; Barone, Martina; Ricci, Francesca; Auteri, Giuseppe; Corradi, Giulia; Fabbri, Francesco; Papa, Valentina; Bandini, Erika; Cenacchi, Giovanna; Tazzari, Pier Luigi; Vianelli, Nicola; Turroni, Silvia; et al. (Frontiers in Oncology, 2021)
Polycythemia Vera (PV) is a myeloproliferative neoplasm with increased risk of thrombosis and progression to myelofibrosis. Chronic inflammation is commonly observed in myeloproliferative neoplasms including PV. The inflammatory network includes the extracellular vesicles (EVs), which play a role in cell-cell communication. Recent evidence points to circulating microbial components/microbes as potential players in hemopoiesis regulation. To address the role of EVs in PV, here we investigated phenotype and microbial DNA cargo of circulating EVs through multidimensional analysis. Peripheral blood and feces were collected from PV patients (n=38) and healthy donors (n=30). Circulating megakaryocyte (MK)- and platelet (PLT)-derived EVs were analyzed by flow cytometry. After microbial DNA extraction from feces and isolated EVs, the 16S rDNA V3-V4 region was sequenced. We found that the proportion of circulating MK-derived EVs was significantly decreased in PV patients as compared with the healthy donors. By contrast, the proportion of the PLT-derived EVs was increased. Interestingly, PV was also associated with a microbial DNA signature of the isolated EVs with higher diversity and distinct microbial composition than the healthy counterparts. Of note, increased proportion of isolated lipopolysaccharide-associated EVs has been demonstrated in PV patients. Conversely, the gut microbiome profile failed to identify a distinct layout between PV patients and healthy donors. In conclusion, PV is associated with circulating EVs harbouring abnormal phenotype and dysbiosis signature with a potential role in the (inflammatory) pathogenesis of the disease.